Feasibility of percutaneous dural sac puncture via a posterior trans-sacral foraminal conduit approach: a CT morphometric analysis - Dhawan, Siddhant S.; Necker, Fabian N.; Massoud, Tarik F. (Neuroradiology, 2023)
We assess the theoretical feasibility of percutaneous posterior sacral foramen (pSF) needle puncture of the sacral dural sac (DS) by studying the three-dimensional imaging anatomy of pSFs relative to the sacral canal (SC). On CT images of 40 healthy subjects, we retrospectively studied sacral alae passageways from SC to pSFs in all three planes to determine if an imaginary spinal needle could theoretically traverse S1 or S2 pSFs in a straight path toward DS. If not straight, we measured multiplane angulations and morphometrics of this route. We found no straight connections between S1 or S2 pSFs and SC. Instead, there were bilateral spatially complex dorsoventral M-shaped "foraminal conduits" (FCs; common, ventral, and dorsal) from SC to anterior SFs and pSFs that would prevent percutaneous straight needle puncture of the DS. This detailed knowledge of the sacral FCs will be useful for accurate imaging interpretation and interventional procedures on the sacrum.
CRIS-Team WoS Importer:2023-04-28